Australia : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1997)
This paper reviews developments in the Australian economy during the prolonged expansion of the 1990s. The focus is on developments in the real sector, public finances, monetary policy, and the balance of payments during 1996-97. The paper reviews longer-term developments in the labor market in Australia, examining the causes of the trend rise in unemployment. In particular, it examines the role played by the traditional, centralized industrial relations system and discusses the efforts to encourage enterprise bargaining and establish a more flexible labor market.